MENDORONG PERTUMBUHAN EKONOMI LOKAL: PENDEKATAN DEBIROKRATISASI UNTUK PENGEMBANGAN UMKM DI KOTA BAUBAU - Ade Saputra, Irwan; Purna, Zarni Adia (Politeknik STIA LAN Makassar, 2024)
This research aims to examine the pattern of debureaucratization in the activities carried out by the government to support SMEs. The research method used is qualitative research with an exploratory type. Findings indicate that debureaucratization measures, such as utilizing digital platforms to empower creative communities, simplifying administrative processes in providing financial support and training, as well as issuing policies supporting SME development, have enhanced accessibility and responsiveness of services for SMEs. However, there are still structural constraints in the SME ecosystem affecting its growth, such as limited access to finance and infrastructure. Moreover, the implementation of policies and programs supporting SMEs is still suboptimal, resulting in limitations on SMEs' contribution to the Gross Regional Domestic Product (GRDP). Further research is recommended to delve deeper into the structural factors influencing SME growth, such as access to finance and infrastructure, and to conduct further evaluation of the implementation of policies and programs supporting SMEs, taking into account the administrative and institutional factors that affect their effectiveness.